Enhancement Of Methane Production From Anaerobic Digestion Of Food Waste By Spent Coffee Ground Derived Biochar - Nurin Arissa, Noor Azmi (2023)
Biogas is a modern energy source and is suitable for necessities of the future with the appropriate application of digestion technology. However, anaerobic digestion (AD) technology still faces some challenges including low methane productivity, instable operation efficiency and undesired refractory substances degradation. Therefore, to overcome this shortcoming, biochar has been recognized as a promising alternative addition in AD process to enhance methane production. Furthermore, biochar derived from biomass is an exceptionally rich wellspring of carbon produced from biomass utilizing thermal combustion. This study aims to characterize biochar as an additive in AD of food waste from spent coffee ground (SCG) biochar and further analyze its performance in AD. To promote the efficiency of the AD, the optimum conditions for biochar dosage, the amount of feedstock and pH value were studied. The experimental findings revealed that 13.528ml/g of biogas yield was achieved under optimum conditions which were 500g of feedstock, 7g of biochar and pH 7, process duration of 14 days. Furthermore, the characterization analysis of SCG biochar showed carbon content was increasing from 54.52% to 87.76%, BET surface area was increasing from 9.2m2/g to 15.3m2/g and contains the -OH, C-H, C-C and C-O functions which enhanced the biogas production in AD. Thus, SCG biochar has potential to enhance methane production and biogas yield in AD of food waste.